Food biodiversity and gastrointestinal cancer risk in nine European countries: analysis within a prospective cohort study - Huybrechts,I; Chimera,B; Hanley-Cook,GT; Biessy,C; Deschasaux-Tanguy,M; Touvier,M; Kesse-Guyot,E; Srour,B; Baudry,J; Berlivet,J; Casagrande,C; Nicolas,G; et al. (European Journal of Cancer, 2024)
BackgroundFood biodiversity in human diets has potential co-benefits for both public health and sustainable food systems. However, current evidence on the potential relationship between food biodiversity and cancer risk, and particularly gastrointestinal cancers typically related to diet, remains limited. This study evaluated how dietary species richness (DSR) was associated with gastrointestinal cancer risk in a pan-European population.MethodsAssociations between DSR and subsequent gastrointestinal cancer risk were examined among 450,111 adults enrolled in the European Prospective Investigation into Cancer and Nutrition cohort (EPIC, initiated in 1992), free of cancer at baseline. Usual dietary intakes were assessed at recruitment with country-specific dietary questionnaires. DSR of an individual’s yearly diet was calculated based on the absolute number of unique biological species in each food and drink item. Associations between DSR and cancer risk were assessed by multivariable Cox proportional hazards regression models.FindingsDuring a median follow-up time of 14.1 years (SD=3.9), 10,705 participants were diagnosed with gastrointestinal cancer. Hazard ratios (HRs) and 95 % confidence intervals (CIs) comparing overall gastrointestinal cancer risk in the highest versus lowest quintiles of DSR indicated inverse associations in multivariable-adjusted models [HR (95 % CI): 0.77 (0.69–0.87); P-value < 0·0001] (Table 2). Specifically, inverse associations were observed between DSR and oesophageal squamous cell carcinoma, proximal colon, colorectal, and liver cancer risk (p-trend<0.05 for all cancer types).InterpretationGreater food biodiversity in the diet may lower the risk of certain gastrointestinal cancers. Further research is needed to replicate these novel findings and to understand potential mechanisms.